Anti Acne Cream Formulation Ethanol Extract of Katuk Leaves (Sauropus androgynus (L.) Merr against Staphylococcus Epidermis and Staphylococcus Aureus - Juvita Herdianty; Arif Wijayanto (Journal of Global Research in Public Health, 2022)
Acne is a skin problem that generally occurs during puberty. Under normal conditions, during puberty, there are Staphylococcus epidermal bacteria and Propionibacterium acnes that proliferate so that inflammation occurs, causing acne on the skin. Since ancient times, our ancestors believed in the use of natural ingredients to treat various diseases, one of which was katuk leaves. Katuk plants have secondary metabolic compounds such as alkaloids, saponins, flavonoids and tannins. The potential of Katuk leaves has been tested for many pharmacological activities, such as antibacterial, antihypertensive, anti-infective, antihyperlipidemic, antianemic and also increases milk production. Katuk leaves are often used in the form of extracts as antibacterial, so it needs to be developed into a pharmaceutical preparation to increase its use. One of the pharmaceutical preparations is cream preparations to treat the causes of acne. This study aims to determine the ability of katuk leaf extract cream to act as an antibacterial against Staphylococcus Epidermis and Staphylococcus Aureus bacteria.. The design of this study is an experimental method, making katuk leaf extract by maceration method by immersing in 70% ethanol solution for 5 days. After 5 days, the pulp and filtrate were separated and then evaporated using a Vacuum Rotary Evaporator to obtain a thick extract. The preparation of katuk leaf extract cream was carried out with a concentration of 10%, 15%, 20% and an antibacterial test was carried out using the pitting method. The antibacterial test results of the katuk leaf cream extract showed an inhibition zone marked with a clear area around the well. Katuk leaf extract cream was able to inhibit the growth of S. aureus and S. epidermis bacteria with the best concentration in formula 3, namely the concentration of katuk leaf extract of 20%.